Comparison of Common Parallel Architectures for the Execution of the Island Model and the Global Parallelization of Evolutionary Algorithms - Limmer, Steffen; Fey, Dietmar (Concurrency and Computation-Practice & Experience, 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.IMMD3.compar

Condor - Limmer, Steffen (Grid-Computing - Eine Basistechnologie für Computational Science, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IMMD.IMMD3.condor

Der modellzentrierte Test geht in die Cloud - Limmer, Steffen; Hofmann, Johannes; et al. (2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.IMMD.IMMD3.dermod

Design of a Highly Parallel Board-Level-Interconnection with 320 Gbps Capacity - Limmer, Steffen; Fey, Dietmar; et al. (Proc. SPIE 8267, 2012)
A parallel board-level interconnection design is presented consisting of 32 channels, each operating at 10 Gbps. The hardware uses available optoelectronic components (VCSEL, TIA, pin-diodes) and a combination of planarintegrated free-space optics, fiber-bundles and available MEMS-components, like the DMD ™from Texas Instruments. As a specific feature, we present a new modular inter-board interconnect, realized by 3D fiber-matrix connectors. The performance of the interconnect is evaluated with regard to optical properties and power consumption. Finally, we discuss the application of the interconnect for strongly distributed system architectures, as, for example, in high performance embedded computing systems and data centers. © 2012 SPIE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD3.design
Keywords: Data center; DMD; Evolutionary algorithm; High density I/O; Integrated free-space optics; MEMS; Modeling; Multi-core architectures; Optical interconnection; Parallel computing

Evolutionary Design of Active Free Space Optical Networks Based on Digital Mirror Devices - Limmer, Steffen; Fey, Dietmar; et al. (Applications of Evolutionary Computation, 2012)
Optical connections have several advantages compared to conventional electrical connections, especially a higher attainable bandwidth. While long distance optical connections are already established, optical board- and chip-level connections are still a subject of current research. In this paper we describe a new setup for optical board-level connections which is based on free space optics and allows the switching of signals within the optical domain. We describe the evolutionary optimization of design parameters for the proposed setup, done with a memetic evolutionary algorithm and present the optimization results. © 2012 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD3.evolut
Keywords: CMA-ES; digital mirror device; Evolutionary algorithm; optical connection; PIFSO

Evolutionary Optimization of Layouts for High Density Free Space Optical Network Links - Limmer, Steffen; Fey, Dietmar; et al. (GECCO '11: Proceedings of the 13th annual conference companion on Genetic and evolutionary computation, 2011)
Electrical chip- and board-level connections are becoming more and more a bottleneck in computation. A solution to that problem could be optical connections, which allow a higher bandwidth. The usage of free space optics can avoid the problem of crosstalk and geometrical signal path crossings in systems with a high density of interconnections. The choice of appropriate design parameters, allowing the realization of such interconnections, is a complicated task. We present an evolutionary algorithm that is able to find these parameters. We describe the parallel execution of that algorithm and present optimization results. Copyright 2011 ACM.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD3.evolut
Keywords: Clos network; Distributed computing; Evolutionary algorithm; Optical interconnect; Optimization; PIFSO

Finite-Differenzen-Methoden - Limmer, Steffen (Grid-Computing - Eine Basistechnologie für Computational Science, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IMMD.IMMD3.finite

Framework for Distributed Evolutionary Algorithms in Computational Grids - Limmer, Steffen; Fey, Dietmar (Advances in Computation and Intelligence, 2010)
In the recent years an increasing number of computational grids have been built, providing an unprecedented amount of computational power. Based on their inherent parallelism, Evolutionary Algorithms are well suited for distributed execution in such grids. Unfortunately, there are several challenges concerning the usage of a grid infrastructure (e.g. the synchronization and submission of jobs and file transfer tasks). In this paper we present a new framework which makes a Globus based grid easily accessible for Evolutionary Algorithms and takes care of the parallelization. The usability is demonstrated by the example of an Evolutionary Algorithm for the Traveling Salesman Problem. © 2010 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD3.framew
Keywords: Computational Grid; Distributed Evolutionary Algorithm; Globus Toolkit; Traveling Salesman Problem

Globus-Webservices - Limmer, Steffen (Grid-Computing - Eine Basistechnologie für Computational Science, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IMMD.IMMD3.globus

GPU implementation of a multiobjective search algorithm - Limmer, Steffen; Fey, Dietmar; Jahn, Johannes (Positivity, 2012)
In this paper we observe the possibility to accelerate a search algorithm for multiobjective optimization problems with help of a graphics processing unit. Besides an implementation we present test results for it and the conclusions that can be drawn from these results. © 2012 Springer Basel AG.
UnivIS-Import:2015-03-09:Pub.2012.nat.dma.pama21.gpuimp
Keywords: CUDA; GPGPU; Multiobjective search algorithm; Optimization; Parallelization

GPU Implementation of a Multiobjective Search Algorithm - Limmer, Steffen; Fey, Dietmar; Jahn, Johannes (2011)
UnivIS-Import:2016-06-30:Pub.2011.tech.IMMD.IMMD3.gpuimp

i3sched Ein OpenNebula Scheduler für die Oracle Grid Engine - Ditter, Alexander; Limmer, Steffen; Fey, Dietmar (Grid-, Cloud und Big-Data Technologien für Systementwurf und -analyse, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD3.i3sche

Investigation of Strategies for an Increasing Population Size in Multi-objective CMA-ES - Limmer, Steffen; Fey, Dietmar (IEEE Congress of Evolutionary Computation 2016 Proceedings, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.IMMD.IMMD3.invest

Modellzentrierter Test in virtualisierten Testumgebungen - Ditter, Alexander; Limmer, Steffen; Fey, Dietmar; Pruksch, Matthias (2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD3.modell

Performance Investigation and Tuning in the Interoperable Cloud4E Platform - Limmer, Steffen; Fey, Dietmar; et al. (Euro-Par 2014 Workshop, Part II, 2014)
The paradigm of Software as a Service (SaaS) offers an interesting option to vendors of simulation software for providing their applications to a wide circle of customers. However, this imposes a challenge to vendors whose applications exist only as classical desktop tools, so far: Interfaces for the remote control have to be provided which are as independent from the underlying cloud infrastructure as possible in order to avoid vendor lock-ins. We present an interoperable platform developed in the project Cloud4E (Trusted Cloud Computing for Engineering), which allows the provisioning of existing simulation software in form of a service in a cloud. The interoperability of the platform and of the services is achieved by the usage of the Open Cloud Computing Interface (OCCI) together with the Advanced Message Queuing Protocol (AMQP) where OCCI is not only used as interface to Infrastructure as a Service (IaaS) but also as interface to SaaS. Hence, the OCCI server plays a central role within the platform and can quickly become a bottleneck, which degrades the performance of the whole platform. We present detailed performance investigations and suggest options to improve the performance. The investigations were performed on the widely used OCCI server implementation called rOCCI server connected to the OpenNebula cloud middleware.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD3.perfor
Keywords: CAE; Cloud; Cloud4E; OCCI; OpenNebula; ROCCI server

Performance Investigations of Genetic Algorithms on Graphics Cards - Hofmann, Johannes; Limmer, Steffen; Fey, Dietmar (Swarm and Evolutionary Computation, 2013)
Genetic algorithms are one of the most adaptable optimization algorithms. Due to their inherent parallelism they seem well suited for the execution on massively parallel hardware such as graphics processing units. In this paper we put this claim to the test by performing comprehensive experiments. We try to find out how well graphics processing units are suited for the task and what parts of genetic algorithms should be executed on them. We focus especially on the new Fermi generation of Nvidia graphics chips. While it is imperative the fitness function be effectively parallelizable on the GPU, because it is the most computational expensive task of the algorithm, results indicate that if this is the case, speedups of several orders of magnitude are possible compared to conventional multi-core CPUs. Our findings also suggest that, starting with the Fermi architecture, all parts of a genetic algorithm should be carried out on the graphics card instead of only part of it. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD3.perfor
Keywords: Evolutionary computing; Fermi; Genetic algorithm; GPU; Traveling salesman; Weierstrass function

Performance-Untersuchungen im Multi-Cluster-Grid - Limmer, Steffen (Grid-Computing - Eine Basistechnologie für Computational Science, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IMMD.IMMD3.perfor_6

Porting of the transfer-matrix method for multilayer thin-film computations on graphics processing units - Limmer, Steffen; Fey, Dietmar (Optical Engineering, 2013)
Thin-film computations are often a time-consuming task during optical design. An efficient way to accelerate these computations with the help of graphics processing units (GPUs) is described. It turned out that significant speed-ups can be achieved. We investigate the circumstances under which the best speed-up values can be expected. Therefore we compare different GPUs among themselves and with a modern CPU. Furthermore, the effect of thickness modulation on the speed-up and the runtime behavior depending on the input data is examined. © 2013 Society of Photo-Optical Instrumentation Engineers.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD3.portin_7

Services for numerical simulations and optimisations in grids - Limmer, Steffen; Fey, Dietmar; et al. (International Journal of Parallel, Emergent and Distributed Systems, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD3.servic_6

Services for Numerical Simulations and Optimizations in Grids - Limmer, Steffen; Fey, Dietmar; et al. (Proceedings of 2012 2nd IEEE International Conference on Parallel, Distributed and Grid Computing (PDGC), 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD3.servic

Service zum Start von Grid-Jobs in virtuellen Machinen - Limmer, Steffen; Fey, Dietmar (4. Workshop Grid-Technologie für den Entwurf technischer Systeme, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD3.servic

Sicherheit im Grid - Limmer, Steffen (Grid-Computing - Eine Basistechnologie für Computational Science, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IMMD.IMMD3.sicher

Simulation and Optimized Design of High Density Optical Crossconnect Systems for Massively Parallel Computing Architectures - Limmer, Steffen; Fey, Dietmar; et al. (Proceedings of the Third International Conference on Optical Supercomputing, 2011)
We demonstrate the simulation results of a skewless high density approach for a multi-channel optical cross connect using integrated free-space optics. Using the 3D nature of free-space optics, this approach is able to solve geometrical problems with static crossings of the signal paths that occur in waveguide optical and electrical interconnection, especially for large number of connections. © 2011 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD3.simula
Keywords: Clos networks; Evolutionary Algorithm; High density I/O; high performance planar optical interconnection; modeling simulation and evaluation techniques; optical interconnections for parallel computing; optimization; parallelization of simulation; skewless parallel gigabit/s interconnections

Softwaresysteme für den Betrieb von Grids - Limmer, Steffen (Grid-Computing - Eine Basistechnologie für Computational Science, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IMMD.IMMD3.softwa

Test@Cloud - A Platform for Test Execution in the Cloud - Limmer, Steffen; Ditter, Alexander; Fey, Dietmar; Pruksch, Matthias; Braun, Christopher; Drescher, Florian; Beißer-Dresel, Martin (Parallel-Algorithmen und Rechnerstrukturen, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD3.testcl

Testen in der Cloud - Automatisiertes Testen in virtualisierten Umgebungen - Ditter, Alexander; Pruksch, Matthias; Limmer, Steffen; Fey, Dietmar (Elektrotechnik, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD3.testen

Three-Dimensional Crossbar Interconnection Using Planar-Integrated Free-Space Optics and Digital Mirror-Device - Limmer, Steffen; Fey, Dietmar; et al. (Optoelectronic Integrated Circuits XIII (Proceedings Volume), 2011)
We consider the implementation of a dynamic crossbar interconnect using planar-integrated free-space optics (PIFSO) and a digital mirror-device™ (DMD). Because of the 3D nature of free-space optics, this approach is able to solve geometrical problems with crossings of the signal paths that occur in waveguide optical and electrical interconnection, especially for large number of connections. The DMD device allows one to route the signals dynamically. Due to the large number of individual mirror elements in the DMD, different optical path configurations are possible, thus offering the chance for optimizing the network configuration. The optimization is achieved by using an evolutionary algorithm for finding best values for a skewless parallel interconnection. Here, we present results and experimental examples for the use of the PIFSO/DMD-setup.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD3.threed
Keywords: Crossbar networks; Evolutionary algorithm; High density I/O; Integrated free-space optics; MEMS; Modeling and simulation; Optical interconnection; Optimization; Parallel computing

Vergleich gebräuchlicher Parallelrechensysteme für die Beschleunigung evolutionärer Algorithmen demonstriert für den Entwurf miniaturisierter optischer und elektronischer Bauelemente - Limmer, Steffen (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
UnivIS-Import:2016-07-26:Pub.2015.tech.IMMD.IMMD3.vergle

VHDL-Simulationen - Beispiel einer High-Throughput-Anwendung im Grid - Limmer, Steffen (Grid-Computing - Eine Basistechnologie für Computational Science, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IMMD.IMMD3.vhdlsi

Wave guiding properties of ribbed surface waveguides in three frequency domains - Limmer, Steffen; Fey, Dietmar; et al. (Optical and Quantum Electronics, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.IMMD.IMMD3.wavegu